2011
DOI: 10.1002/jbmr.426
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitor MS-275 stimulates bone formation in part by enhancing Dhx36-mediated TNAP transcription

Abstract: Histone deacetylases (HDACs) deacetylate both histones and nonhistone proteins and play a key role in the regulation of physiologic and aberrant gene expression. Inhibition of HDACs has emerged as a promising therapeutic target for cancer and neurologic diseases. In this study we investigated the osteogenic effect and mechanism of action of MS-275, a class I HDAC inhibitor with preference for HDAC1. Both local and systemic administration of MS-275 stimulated bone regeneration in animal models. MS-275 stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 54 publications
6
39
0
Order By: Relevance
“…Although the structural and biophysical characterization of G-quadruplexes has progressed rapidly, the mechanistic basis for their recognition and remodeling is poorly understood. RHAU has emerged as a primary quadruplex resolvase in eukaryotic cells, and the functional consequences of quadruplex remodeling has been established in a small number of important processes (17,18,21,41,42). Therefore, our goal was to make biophysical inroads to the process by examining the recognition of G-quadruplexes by the N-terminal region of RHAU that contains the RSM, a required region for quadruplex recognition.…”
Section: Discussionsupporting
confidence: 44%
“…Although the structural and biophysical characterization of G-quadruplexes has progressed rapidly, the mechanistic basis for their recognition and remodeling is poorly understood. RHAU has emerged as a primary quadruplex resolvase in eukaryotic cells, and the functional consequences of quadruplex remodeling has been established in a small number of important processes (17,18,21,41,42). Therefore, our goal was to make biophysical inroads to the process by examining the recognition of G-quadruplexes by the N-terminal region of RHAU that contains the RSM, a required region for quadruplex recognition.…”
Section: Discussionsupporting
confidence: 44%
“…Moreover, there is a need to optimize bone tissue-engineering strategies for the treatment of non-union fractures and critical size defects. Numerous laboratories have reported that HDIs enhance osteoblast differentiation in vitro (11)(12)(13)(14)(15)(35)(36)(37). In this study, we characterized epigenetic events that occur in SAHA-treated osteoblasts to understand the pathways that control osteoblast differentiation.…”
Section: Discussionsupporting
confidence: 42%
“…The fact that many cells can readily take up G4DNA indicates that this mechanism may also allow the cell to respond to its external environment as well as internal stress (67,72). Although our results suggest important roles for G4DNA in the regulation of cytoplasmic cellular processes, other studies have suggested roles for G4DNA in modulating transcription through the binding of helicases such as DHX36 (30,96,97), the RecQ family helicases (98,99), and the XPB and XPD helicases (75). It is possible that any G4DNA-binding protein may be regulated by freely diffusing G4DNA, leading to various cellular responses based on the large number of proteins that are reported to have G4DNA binding capacity (4, 100 -102).…”
Section: Discussionsupporting
confidence: 41%